2014
DOI: 10.2196/jmir.2630
|View full text |Cite
|
Sign up to set email alerts
|

Online Activity and Participation in Treatment Affects the Perceived Efficacy of Social Health Networks Among Patients With Chronic Illness

Abstract: BackgroundThe use of online health-related social networks for support, peer-to-peer connections, and obtaining health information has increased dramatically. Participation in an online health-related social network can enhance patients’ self-efficacy and empowerment, as they are given knowledge and tools to manage their chronic health condition more effectively. Thus, we can deduce that patient activation, the extent to which individuals are able to manage their own health care, also increases. However, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…First, it suggests that telehealth interest is likely to increase over time as the population, as a whole, becomes more familiar with and comfortable using different forms of technology. This may be particularly true of social media-based telehealth, 218 the newest type of technology included in the survey and also the technology that respondents reported least confidence and interest in using. Following on from this, as our results revealed that technology confidence was modality specific, whereby confidence using one type of technology was related only to interest in using that same form of telehealth, it suggests that willingness to use telehealth is not restricted to patients who are confident using technology in general.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…First, it suggests that telehealth interest is likely to increase over time as the population, as a whole, becomes more familiar with and comfortable using different forms of technology. This may be particularly true of social media-based telehealth, 218 the newest type of technology included in the survey and also the technology that respondents reported least confidence and interest in using. Following on from this, as our results revealed that technology confidence was modality specific, whereby confidence using one type of technology was related only to interest in using that same form of telehealth, it suggests that willingness to use telehealth is not restricted to patients who are confident using technology in general.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…The PAM-13 has been translated and validated in several languages including Dutch [14] , Danish [15] , Spanish [16] , and German [17] . A Hebrew translation has been used in studies of primary care patients [18] and participants in a social health network for persons with chronic disease [19] . However, the psychometric properties of the Hebrew translation have not been heretofore assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent studies show that 60 % of the population search for medical information on social networks, that 29 % actively participate in sharing contents, and that 20 % of the subjects discussed in social networks are focused on health topics [20]. Furthermore, a study by Magnezi et al [13] showed that people suffering from eating disorders are particularly interested by social health networking.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent characteristics of the Websurfer patient are female gender, younger age, a chronic illness, and a high level of education. With regard to the topics of interest, besides general information about a specific disease, patients appreciate using social networks [13] in order to share experiences with other patients and give or receive emotional support. In this context, obese people seeking bariatric surgery could match with this profile.…”
Section: Introductionmentioning
confidence: 99%